Wild rain - Feehan, Christine. frey50 (New York : Jove, 2004)
Finding a safe haven in the rain forest from a relentless killer, Rachael, armed with a new identity, finds her peace shattered by Rio, an exotic native of the forest who harbors a dark secret.
Keywords: Man-woman relationships -- Fiction; Attempted assassination; Rain forests -- Fiction; Romance fiction; Attempted assassination; Man-woman relationships; Rain forests; Romance fiction; Fiction